2013
DOI: 10.1002/2013gl057880
|View full text |Cite
|
Sign up to set email alerts
|

Rupture model of the 2011 Mineral, Virginia, earthquake from teleseismic and regional waveforms

Abstract: [1] We independently invert teleseismic P waveforms and regional crustal phases to examine the finite fault slip model for the 2011 M w 5.8 Mineral, Virginia, earthquake. Theoretical and empirical Green's functions are used for the teleseismic and regional models, respectively. Both solutions show two distinct sources each about 2 km across and separated by 2.5 km. The source at the hypocenter is more localized in the regional model leading to a higher peak slip of 130 cm and higher average stress drop of 250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
1
26
0
3
Order By: Relevance
“…Stress drop values of the order of 10 1 MPa inferred from finite‐fault models have also been reported for inland earthquakes. High average stress drop values have also been estimated for earthquakes in the United States, such as 25 MPa for the 2011 Virginia earthquake ( M w 5.8) (Hartzell, Mendoza, & Zeng, ) and 78 MPa for the 2016 Borrego Springs, CA earthquake ( M w 5.2) (Ross et al, ). For M w 2‐class events on the San Andreas Fault in the Parkfield area, CA, the high peak stress drop values of 65–94 MPa have been estimated (Dreger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress drop values of the order of 10 1 MPa inferred from finite‐fault models have also been reported for inland earthquakes. High average stress drop values have also been estimated for earthquakes in the United States, such as 25 MPa for the 2011 Virginia earthquake ( M w 5.8) (Hartzell, Mendoza, & Zeng, ) and 78 MPa for the 2016 Borrego Springs, CA earthquake ( M w 5.2) (Ross et al, ). For M w 2‐class events on the San Andreas Fault in the Parkfield area, CA, the high peak stress drop values of 65–94 MPa have been estimated (Dreger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than deconvolving the instrument response from the earthquake records, we convolved the synthetics with the appropriate instrument response. This approach has previously been used to minimize the introduction of low‐frequency noise into the time series data (Hartzell et al, ; Sun & Hartzell, ). No other filtering is performed to preserve waveform details.…”
Section: Methodsmentioning
confidence: 99%
“…The stress drops inferred for the Prague sequence are significantly lower than the 15–25 MPa stress drops observed for the 2011 M w 5.8 Mineral, Virginia, earthquake using similar techniques with regional and teleseismic waveforms [ Hartzell et al , ], the ~14–25 MPa stress parameter observed for the eastern U.S. based on pseudospectral acceleration (PSA) ground motion data [ Atkinson and Boore , ; Boore et al , ], and the median 19 MPa Brune model stress drop modeled with empirical Green's functions (EGFs) for the 2002 M 5 Au Sable Forks, NY, earthquake sequence [ Viegas et al , ]. We note that model assumptions between studies are important and may yield dramatic differences in stress drop values, which may hinder direct comparisons [e.g., Abercrombie and Rice , ].…”
Section: Introductionmentioning
confidence: 99%